Crossing boundaries & confounding identity : Chinese women in literature, art, and film - Hughes, Cheryl D., 1945- (Albany : State University of New York Press, 2023)
"Examines literary, historical, and cultural portrayals of Chinese women, across centuries and continents"--
The Beginnings of the Cultural and Moral Landscape -- History from the Top Down: the Dowager Empress -- History from the Bottom Up: The Peasantry -- From Footbinding and Concubinage to the Anti-Footbinding Movement -- From the Anti-Footbinding Movement to Women in the State -- Love and Marriage -- From Marriage to Family Reverence -- Large-Scale Tragedies -- "The World Is Yours": Mao's Promises and Deng's Fulfillment of Promises -- One Child Only or Fertility Control -- The Revenge: China's Leftover Women -- Conclusion -- Notes -- Works Cited -- Index
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on March 07, 2023).
JSTOR
Keywords: Women -- China; Women in literature; Women in art; Women in motion pictures; Femmes -- Chine; Femmes dans la littérature.; Femmes dans l'art.; Femmes au cinéma.; SOCIAL SCIENCE / Ethnic Studies / Asian Studies; Women; Women in art; Women in literature; Women in motion pictures; China